METODE PEMAHAMAN DAN PENGAMALAN HADITS JAMAAH TABLIGH - Zaki, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2015)
There are clear differences in meaning of the Prophetictraditions (hadith) among the Islamic scholars. Accordingto scholars of Hadith (muhaddits), everyting that comesfrom the Prophet, in the form of words, deeds, taqrir,physical and non-physical, since before his apostleshipand after it, is a Hadith or Sunnah, which should befollowed. As for the scholars of fiqh (fuqaha), hadith islimited on words, deeds, and taqrir taht only has a legalimplications. The deeds of the Prophet which isperformed for the basic needs as human beings, thedeeds that was done by accident, physical form, are nothadith. Among Muslims, Tablighi Jamaat is thecommunity that tends to the defination the scholars ofhadith, so they practices and strives for such outwardappearance of the Prophet. Tablighi Jamaat are generallytextual. It can be seen from the practice of the sunnahsthat related to worship, manners or appearance, such ashow to dress, wearing a cap and turban, siwak,lengthening the beard and shaving the mustache, eatingand drinking, and others. For them, the Prophet was sentas an example for humanity, so that everything thatcomes from him should be followed